INTEGRATION OF THE PROBLEM-BASED LEARNING SYSTEM INTO THE PROFESSIONAL LANGUAGE MODULE AT THE LITHUANIAN UNIVERSITY OF HEALTH SCIENCES - Dulksnienė, Liudmila; Ramanauskas, Irmantas; Kazlauskaitė, Daina; Kosova, Sveta (Sustainable Multilingualism / Darnioji daugiakalbystė, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*284.35px); top: calc(var(–scale-factor)*75.38px); font-size: calc(var(–scale-factor)*6.96px); font-family: sans-serif; transform: scaleX(1.15355);" role="presentation">http://dx.doi.org/10.7220/2335-2027.8.10 As the significance of science increases and the cooperation with foreign partners becomes more intensive, education and training of highly qualified specialists gains its importance. At the Lithuanian University of Health Sciences, update and improvement of the curriculum are priority fields in the education and training of health specialists. The field of professional languages is the field that attracts special attention. The University should educate specialists who would be able to cooperate in research and professional activity via free communication in several foreign languages. This study aimed at revealing the peculiarities of the expression of the elements of the problem-based learning system in professional language studies at the Lithuanian University of Health Sciences (LSMU). The generalized results of the study showed that the formation of students’ deep approach to studies and their independent work skills may be affected by integrating the elements of the problem-based learning system into the studying process. Empowering the students for successful studies was significantly facilitated by the application of such techniques as mind maps, group work, problem solving, brainstorming, and discussion.